If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + -45 = 39 Reorder the terms: -45 + X = 39 Solving -45 + X = 39 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '45' to each side of the equation. -45 + 45 + X = 39 + 45 Combine like terms: -45 + 45 = 0 0 + X = 39 + 45 X = 39 + 45 Combine like terms: 39 + 45 = 84 X = 84 Simplifying X = 84
| 4x-40=-5x+32 | | 39=45-x | | 20=52*2-12 | | 4x-40=5x+32 | | 2(10-b)=b+50 | | 8m-11+m-2=5 | | -4x-40=-5x+32 | | 3n^2+1=0 | | 8.8x+19-8.9x-4.8= | | 4p-2p=12-2p+7p | | 5(a-3)=30+2a | | (X-5)10+(1-2x).5=(3-x).4 | | 7xs+27=139 | | -9x+36=-4x+81 | | 1+8k+k=6+7k+3k | | 6w-3=5w-7 | | 1+8k+k=6+7+3k | | 15r^2+8r+1=0 | | -9x+14=-2x+63 | | 3x-54=-9x+18 | | 99x-115=30 | | 5n^2+36+36=0 | | -0.3(0.7x-0.9)=-1.3 | | 12m^2-18m-84=0 | | -4m+5m=5m+16 | | 2x-60=-10x+12 | | 3a-10=a+2 | | b^2+4=-5b | | 4(-1+7p)=-88 | | log(13)+log(15)= | | p^3-3p^2q-54pq^2=0 | | n^2+20=-9n |